(untitled) (REMUNOM, 2024)
Digital advertising plays a crucial role in promoting transparency and legality in public works bidding processes, offering citizens access to relevant information and enabling more effective monitoring of these procedures. This study investigates how digital advertising can be used to enhance transparency and legality in public works bidding from the citizens’ perspective. The analysis focuses on the importance of transparency in administrative processes, the relevance of the Fiscal Responsibility Law, and the impact of technologies on promoting more transparent and efficient public governance. Additionally, the research highlights the effectiveness of transparency portals and interactive digital platforms in facilitating social oversight and fostering a culture of citizen participation. The findings provide an understanding of the benefits, challenges, and opportunities associated with the use of digital advertising in public bidding processes, offering practical recommendations to optimize its use and strengthen citizen participation